EVALUASI PENGEMBANGAN KOPERASI SERBA USAHA (STUDI KASUS PADA KOPERASI SATMAKURA DI KABUPATEN KEPAHIANG TAHUN 2014) - Marida Sariningsih; Bayu Risdiyanto (Professional: Jurnal Komunikasi dan Administrasi Publik, 2017)
The main problems in this research was the development of Cooperative goal as the pillar of national economic development or as an institution which a healthy economy just was not happening. Accordingly, The Kepahiang District has developed a cooperative which name is “Satmakura Cooperative” as a ground breaking effort in cooperative development policy. Method and approach of research were conducted by qualitative research method with a descriptive approach. The results of evaluation showed that the development cooperation through strategies and models and approaches that involve elements of community leaders and local government officials led to the development of co-operatives became easier to execute. With intensive involvement of government officials with community leaders, local government officials then initiated and cooperative management,  until slowly a number of important management left to the professionals. And the impact and results of the development has been occurred, visible from a number of changes and the real benefits as seen from the increasing number of cooperative members, the increasing scale of business, the infrastructure is good (complete), an increasingly diversified integrated technical and marketing attainment is getting better and wider. Tangible results and impact show that the development of cooperative organizations are conducted in a relatively successful local government to achieve its objectives.